Bones of Free-Living Ungulates as Indicators of Environmental Contamination by Mercury: A Comparative Study between the Western Carpathians and Zhongar Alatau - Zábojníková Lenka; Feješ Samuel; Oxikbayev Berikzhan; Kasymkhanova Togzhan; Janiga Marián; Ballová Zuzana Kompišová (Ekológia (Bratislava), 2025)
We monitored the variability of mercury concentration in bones from naturally deceased or predator-caught ungulates from the Western Carpathians (Slovakia) and Zhongar Alatau (Kazakhstan), including red deer, roe deer, Tatra chamois, horse, Asiatic ibex, Marco Polo sheep, and other Bovidae. These species, as herbivores, have the advantage of a low trophic level, which implies a lower degree of mercury accumulation in the food chain. We compared the extent to which concentrations differed by location and habitat type. Mercury concentrations were determined by a DMA-80 analyzer. Lower mean concentrations observed in bones from Kazakhstan (0.0024 mg kg−1 dry weight) than from Slovakia (0.0063 mg kg-1 dry weight) suggest a lower level of ecosystem contamination from anthropogenic sources. The influence of habitat proved to be nonsignificant. Although bones are not a target organ for mercury accumulation, they reflect the state of environmental pollution and can be used in noninvasive retrospective environmental monitoring methods.